Aortic Valve Replacement with a Conventional Stented Bioprosthesis versus Sutureless Bioprosthesis: a Study of 763 Patients - Syed Saleem Mujtaba (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: The aim of this retrospective study was to compare early postoperative outcomes after aortic valve replacement (AVR) with sutureless bioprostheses and conventional stented bioprostheses implanted through median sternotomy. Methods: From January 2011 to December 2016, 763 patients underwent aortic valve replacement with bioprostheses; of these, 139 received a Perceval S sutureless valve (Group A) and 624 received a Perimount Magna Ease valve (Group B). These groups were further divided into A1 (isolated Perceval AVR), A2 (Perceval AVR with coronary artery bypass grafting [CABG]), B1 (isolated conventional stented bioprosthesis), and B2 (conventional stented bioprosthesis + CABG). Results: Patients in Group A were older (mean 74 years vs. 71 years; P<0.0001), predominantly women (53% vs. 32%; P<0.0001), had a higher logistic EuroSCORE (3.26 vs. 2.43; P<0.001), more preoperative atrial fibrillation (20% vs. 13%; P=0.03), and had a lower reopening rate for bleeding (2.1% vs. 6.7%; P=0.04). Compared to Group B1, Group A1 had shorter cross-clamp (mean 40 min vs. 57 min; P≤0.0001) and bypass times (mean 63 min vs. mean 80 min; P=0.02), and they bled less postoperatively (mean 295 ml vs. mean 393 ml; P=0.002). The mean gradient across Perceval valve was 12.5 mmHg while its effective orifice area was 1.5 cm2. Conclusion: In our retrospective study of 763 patients, sutureless valve group patients are older, mostly women, more symptomatic preoperatively, and have higher logistic EuroSCORE. They have shorter cross-clamp and bypass times, less postoperative bleeding, and reduced incidence of reopening. Further studies are needed to evaluate the clinical benefits in short, mid, and long-terms.